Woc (without children) gene control of ecdysone biosynthesis in Drosophila melanogaster. - Warren, J.T.; Wismar, J.; Subrahmanyam, B.; Gilbert, L.I. (Molecular and Cellular Endocrinology, 2001)
The first step in ecdysteroidogenesis, i.e. the 7,8-dehydrogenation of dietary cholesterol (C) to 7-dehydrocholesterol (7dC), is blocked in Drosophila melanogaster homozygous woc (without children) third instar larval ring glands (source of ecdysone). Unlike ring glands from wild-type D. melanogaster larvae, glands from woc mutants cannot convert radiolabelled C or 25-hydroxycholesterol (25C) to 7dC or 7-dehydro-25-hydroxycholesterol (7d25C) in vitro, nor to ecdysone (E). Yet, when these same glands are incubated with synthetic tracer 7d25C, the rate of metabolism of this polar Delta(5,7)-sterol into E is identical to that observed with glands from comparably staged wild-type larvae. The absence of this enzymatic activity in vivo is probably the direct cause of the observed low whole-body ecdysteroid titers in late third instar homozygous mutant larvae, the low ecdysteroid secretory activity in vitro of brain-ring gland complexes from these animals, and the failure of the larvae to pupariate (undergo metamorphosis). Oral administration of 7dC, but not C, results in a dramatic increase in ecdysteroid production both in vivo and in vitro by the woc mutant brain-ring gland complexes and affects a partial rescue to the beginning of pupal-adult development, but no further, despite elevated whole-body ecdysteroid titers. Data previously reported (Wismar et al., 2000) indicate that the woc gene encodes a zinc-finger protein that apparently modulates the activity of the 7,8-dehydrogenase.